2010
DOI: 10.1063/1.3431459
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy and metal-insulator transition in SrRuO3 thin films at different growth temperatures

Abstract: Articles you may be interested inCrossover of angular dependent magnetoresistance with the metal-insulator transition in colossal magnetoresistive manganite films Appl. Phys. Lett. 95, 132506 (2009); 10.1063/1.3240407 Magnetoresistive anisotropy and magnetoresistivity in strained La 0.65 Ca 0.35 Mn O 3 films near the metalinsulator transition Appl. Phys. Lett. 90, 232506 (2007); 10.1063/1.2746956 Suppression of the metal-insulator transition temperature in thin La 0.7 Sr 0.3 Mn O 3 films J. Appl. Phys. 96, 638… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…9,21, 22 We find T C values of 153.5 K for the T1-type samples, a value which is slightly smaller than the SRO bulk value of about 160 K. 23 The C-type and I-type samples have a T C of 149.1 and 150.0 K, respectively. We note that the conducted measurements of T C in remanence provides lower values than in-field measurements.…”
Section: B Magnetismmentioning
confidence: 67%
“…9,21, 22 We find T C values of 153.5 K for the T1-type samples, a value which is slightly smaller than the SRO bulk value of about 160 K. 23 The C-type and I-type samples have a T C of 149.1 and 150.0 K, respectively. We note that the conducted measurements of T C in remanence provides lower values than in-field measurements.…”
Section: B Magnetismmentioning
confidence: 67%
“…26,31 Therefore, the decrease of T C in our SRO films can be attributed to the weakened ferromagnetic interaction due to the modulation of Ru-O-Ru bonds as c is expanded. 20,32 In the hysteresis curves, the magnetization shows jumps at different field, which is generally attributed to the Barkhausen jump. 33 These jumps are commonly caused by the irreversible motion of the domain walls between two regions of opposite magnetizing forces.…”
Section: 905å) Is Strained Compressively a Small Signal Belonging mentioning
confidence: 99%
“…The larger structure distortion induced by the He ion irradiation leads to a change in the spin-spin coupling, which results in changes in the spinsplit electronic band structure and the exchange energy among spins. 32,[36][37] In addition to the variation of spin-spin coupling, the change of magnetic anisotropy as the component of T-like phase increases can also contribute to the decrease of magnetization. Having established that material structures and magnetic phases are susceptible to ion irradiation, we next study whether the EB effect can be introduced in a single SRO layer.…”
Section: 905å) Is Strained Compressively a Small Signal Belonging mentioning
confidence: 99%
“…[7][8][9] Previous studies have established that transport and magnetic properties of this compound are very sensitive to surface morphology, growth temperature, and substrate induced strain. [10][11][12][13][14] Besides the above mentioned factors, thickness of the film also influences its magnetic and electric properties. Toyota et al reported the enhanced resistivity in thin films due to the energy gap at Fermi energy level.…”
mentioning
confidence: 99%
“…This is also supported by the XRD analysis where a tensile strain is noticed in the 12 nm film, which modifies Ru-O-Ru interatomic distances, resulting in resistivity enhancement. 11,26 The insulating behavior induced by disorder in the system follows the variable range hooping model: 27…”
mentioning
confidence: 99%